2022
DOI: 10.3389/fphar.2022.975641
|View full text |Cite
|
Sign up to set email alerts
|

Future insights of pharmacological prevention for AKI post cardiopulmonary bypass surgery (based on PK/PD approach)

Abstract: The incidence of acute kidney injury (AKI) post-cardiopulmonary bypass (CPB) can cause an increase in the rate of renal replacement therapy (RRT) and mortality rate. Compared to brain and liver damage post-CPB, AKI has the highest incidence of 83%. Based on this phenomenon, various efforts have been made to reduce the incidence of AKI post-CPB, both pharmacologically and non-pharmacologically interventions. The purpose of this review is to emphasize several renal protector agents which under optimal conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
1
Order By: Relevance
“…The optimal cutoff value observed in our population was 0.265(ng/mL) 2 / 1,000, which is slightly lower than that of the previous studies, probably because all patients with AKI at any stage 6 h after cardiac surgery were included, not only moderate to severe AKI in the first 12 h. We also found that TIMP-2•IGFBP7, SRI score, and age were associated with AKI within 7 days postoperatively. Generally, the AKI incidence might occur after cardiac surgery as a consequence of CPB utilization [25]. In our study, the time of CPB was not significantly different between AKI and no AKI groups.…”
Section: Prediction Of the Composite Endpointcontrasting
confidence: 48%
“…The optimal cutoff value observed in our population was 0.265(ng/mL) 2 / 1,000, which is slightly lower than that of the previous studies, probably because all patients with AKI at any stage 6 h after cardiac surgery were included, not only moderate to severe AKI in the first 12 h. We also found that TIMP-2•IGFBP7, SRI score, and age were associated with AKI within 7 days postoperatively. Generally, the AKI incidence might occur after cardiac surgery as a consequence of CPB utilization [25]. In our study, the time of CPB was not significantly different between AKI and no AKI groups.…”
Section: Prediction Of the Composite Endpointcontrasting
confidence: 48%
“…In addition, NAC has exhibited important effects by reducing the levels of lactate and nitrogenous slags in the blood 24 h after cardiac surgery with CPB, suggesting a beneficial effect on peripheral and renal tissue perfusion [123]. Furthermore, the prophylactic use of NAC attenuates the liver damage induced by cardiopulmonary bypass during cardiac surgery, in addition to reducing the incidence of acute kidney injury in this type of surgery [93,[124][125][126]. However, more clinical studies are needed to standardize necessary doses and treatment times, as well as monitoring possible unwanted effects.…”
Section: N-acetylcysteinementioning
confidence: 99%